Uma análise dos vídeos publicitários virais mais vistos no site Youtube.com no Brasil e no mundo: um olhar crítico do papel do marketing com ênfase no hiperconsumismo - Souza, Ricardo Araujo de (2014)
This research believes that a relationship exists between the current paradigm crisis in Marketing with a one-dimensional and one-sided view of the relationship of the companies to the market and that theories such as Marketing and Service Co-creation already point to a multidimensional and bilateral vision between the company market and consumers. Even with the new signaling theories to a broader and bilateral, there is a vision myopia , especially in relation to the object of study of the National Marketing. The research believes that this object of study should be the society of hyperconsumption , construct designed by postmodern thinkers . With this construct various multidimensional , complex and dialogical marketing phenomena can be contextualized, such as Viral Marketing. This research then bases its theoretical basis in a model aligned with postmodern ideas about consumerism then to analyze the phenomenon of viral videos on Youtube , with special emphasis on the comparison between most viewed national and international viral video ads